Peran Pendidikan dalam Pelestarian Budaya Bali pada Penerus Muda dan Masyarakat Lokal - Merlina Agustin; Nurito Nurito; Isnaeni Wijayanti; Naila Rizqiah; Laelia Nurpratiwiningsih (Concept: Journal of Social Humanities and Education, 2025)
This research aims to determine the role of education in preserving Balinese culture among young people and local communities. This research uses qualitative research methods with data collection techniques through interviews and observation. The research results show that education has an important role in preserving Balinese culture, especially in increasing awareness and participation of local communities. However, this research also found several challenges faced in preserving Balinese culture through education, such as a lack of integration of Balinese culture in the educational curriculum and a lack of educational resources. This research has implications for the importance of increasing the role of education in preserving Balinese culture and increasing awareness and participation of local communities in preserving Balinese culture.